2014
DOI: 10.3389/fonc.2014.00278
|View full text |Cite
|
Sign up to set email alerts
|

The Early Result of Whole Pelvic Radiotherapy and Stereotactic Body Radiotherapy Boost for High-Risk Localized Prostate Cancer

Abstract: Purpose: The rationale for hypofractionated radiotherapy in the treatment of prostate cancer is based on the modern understanding of radiobiology and advances in stereotactic body radiotherapy (SBRT) techniques. Whole-pelvis irradiation combined with SBRT boost for high-risk prostate cancer might escalate biologically effective dose without increasing toxicity. Here, we report our 4-year results of SBRT boost for high-risk localized prostate cancer.Methods and Materials: From October 2009 to August 2012, 41 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 40 publications
7
35
0
Order By: Relevance
“…BED1.5), compared with a BED1.5 of 154–166 Gy with CF‐EBRT (39–42 fractions of 1.8 Gy). Consistent with dose escalation trials that have showed a lower PSA nadir with increased total dose, we expect the SBRT regimen to produce a lower PSA nadir and a continuative decline of PSA. In our study, the PSA decline of SBRT was not significantly notable in the first year but constantly decreased during the period of 2, 3 and 4 years to achieve lower PSA nadir than that of CF‐EBRT.…”
Section: Discussionsupporting
confidence: 65%
“…BED1.5), compared with a BED1.5 of 154–166 Gy with CF‐EBRT (39–42 fractions of 1.8 Gy). Consistent with dose escalation trials that have showed a lower PSA nadir with increased total dose, we expect the SBRT regimen to produce a lower PSA nadir and a continuative decline of PSA. In our study, the PSA decline of SBRT was not significantly notable in the first year but constantly decreased during the period of 2, 3 and 4 years to achieve lower PSA nadir than that of CF‐EBRT.…”
Section: Discussionsupporting
confidence: 65%
“…Recent studies evaluated the use of stereotactic RT boost to the prostate after standard fractionation pelvic RT in order to escalate biologically effective dose in intermediate-and high-risk prostate cancer (17)(18)(19). With a median follow-up greater than 42 months, limited grade 2 and no grade 3 GI (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…With a median follow-up greater than 42 months, limited grade 2 and no grade 3 GI (17)(18)(19)(20). Firstly, we focused our attention on subclinical mucosal changes instead of clinical symptoms, which can have a different biological evolution over the time, since altered fractionation was used.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies evaluated the use of stereotactic RT boost to the prostate after standard fractionation pelvic RT in order to escalate biologically effective dose in intermediate-and high-risk prostate cancer (17)(18)(19). With a median follow-up greater than 42 months, limited grade 2 and no grade 3 GI (17)(18)(19)(20). Firstly, we focused our attention on subclinical mucosal changes instead of clinical symptoms, which can have a different biological evolution over the time, since altered fractionation was used.…”
Section: Discussionmentioning
confidence: 99%